2017
DOI: 10.1007/s12250-016-3931-1
|View full text |Cite
|
Sign up to set email alerts
|

Current status of severe fever with thrombocytopenia syndrome in China

Abstract: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease caused by SFTS virus (SFTSV). SFTSV is associated with a high mortality rate and has been reported in China, South Korea and Japan. SFTSV undergoes rapid changes owing to evolution, gene mutations, and reassortment between different strains of SFTSV. In this review, we summarize the recent cases and general properties of SFTS, focusing on the epidemiology, genetic diversity, clinical features, and diagnostics of SFTSV in China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
182
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(189 citation statements)
references
References 62 publications
(68 reference statements)
2
182
1
Order By: Relevance
“…Due to a lack of any prophylactic vaccine or effective antivirals, the mortality rate of SFTS cases can reach as high as 30%. SFTS has therefore become a significant public health problem (Liu et al, 2014b;Zhan et al, 2017). Beyond China, SFTS has also been reported in Japan and South Korea in 2013, with a similar case reported in the USA in 2012 (Kim et al, 2013;McMullan et al, 2012;Takahashi et al, 2014), indicative of a potentially global situation requiring control and prevention.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Due to a lack of any prophylactic vaccine or effective antivirals, the mortality rate of SFTS cases can reach as high as 30%. SFTS has therefore become a significant public health problem (Liu et al, 2014b;Zhan et al, 2017). Beyond China, SFTS has also been reported in Japan and South Korea in 2013, with a similar case reported in the USA in 2012 (Kim et al, 2013;McMullan et al, 2012;Takahashi et al, 2014), indicative of a potentially global situation requiring control and prevention.…”
Section: Introductionmentioning
confidence: 97%
“…Currently, almost 10,000 cases of the disease have been reported in 23 provinces and etiologically confirmed in 18 provinces, with numbers increasing yearly ( Fig. 1) (Liu et al, 2014b;Zhan et al, 2017). Due to a lack of any prophylactic vaccine or effective antivirals, the mortality rate of SFTS cases can reach as high as 30%.…”
Section: Introductionmentioning
confidence: 99%
“…Similar viruses have been reported in Japan, Korea and the USA . Although the transmission hosts and vectors remain unclear, the long‐horned tick ( Haemaphysalis longicornis ) is considered the most likely transmission vector . The mechanisms of entry for SFTSV into the patient from a tick‐bite region are not yet fully understood.…”
Section: Introductionmentioning
confidence: 71%
“…In 2009, an emerging infectious disease was reported in China, with major clinical symptoms of fever, thrombocytopenia and leukocytopenia, and a mortality rate of 6–30% . This disease was designated “severe fever with thrombocytopenia syndrome” (SFTS).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the vaccine have published a paper attempting to identify optimal strains for vaccines from the eight main strains of SFTS virus strains in China [3]. According to that paper, it is concluded that HB 29 strain will be optimal as a standard strain for vaccines because of its strong cross-reactivity with heterologous antibodies and high homology in the S segments with other SFTS virus strains.…”
Section: Mini Reviewmentioning
confidence: 99%